NILAI-NILAI PENDIDIKAN KARAKTER TOLERANSI DALAM PERSPEKTIF KH. HASYIM ASY’ARI - Andani Kumalasari; Nur Salim, Mohammad (PAI FAI UNHASY Tebuireng Jombang, 2022)
Abstract: Character education in Islamic education places more emphasis on individual development through the cultivation of commendable morals so that they are able to make themselves as good personal individuals, for those around them and the wider community. The position of character education has a very important role in creating intelligent, tolerant, intelligent and noble characters. Efforts to create a harmonious society must always be jointly endeavored by all components of the nation to build a sense of tolerance towards other people and groups. For the Indonesian people, the term tolerance is actually not a new problem. Because tolerance is one of the characteristics of the Indonesian nation which is accepted as the ancestral heritage of the Indonesian nation itself. The research objectives discussed in the study: To find out the concept of tolerance character education in the perspective of KH. Hasyim Asy'ari in the book Adabul al-Alim waal-Muta'allim. To find out the values ​​of character education in the perspective of KH. Hasyim Asy'ari. To achieve this goal, the researchers used research methods with a qualitative approach. This type of research is library research, namely research whose main object is books or other library sources. Data is searched and found through library studies from books or other sources relevant to the discussion. The results of this study are: observing the life history of KH. Hasyim Asy'ari and several of his writings produced three findings. First, there are ten types of students' character towards themselves. Second, there are twelve types of student character towards educators. Third, it includes thirteen student characters towards the lesson. Keyword: Character education, Tolerance, KH. Hasyim Asy'ari